2012
DOI: 10.1111/hdi.12008
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hemodialysis treatment on the level of DNA strand breaks and oxidative DNA lesions measured by the comet assay

Abstract: Hemodialysis patients have a higher risk for oxidative stress-related complications, such as cardiovascular disease and cancer. The increased level of oxidative stress is due to several factors, e.g., the hemodialysis treatment itself and the uremic state. In the present study, the effects of dialysis treatment on the level of DNA breaks and oxidative DNA lesions in mononuclear cells were measured with the comet assay. Factors possibly affecting DNA damage (reported as % DNA in tail) such as the duration of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The conversion curve provides a better fitting between %T and AU [55,60] and showed negative values of %T for AU below 26, indicating that %T was zero; above 400 AU, the %T was 84%, in accordance with others [55,60]. Our data is in accordance with other studies reporting that the levels of DNA breaks and oxidative DNA lesions, measured by the comet assay, are higher in dialysis patients then in controls [77].…”
Section: Dna Damage In Esrd Patientssupporting
confidence: 91%
See 2 more Smart Citations
“…The conversion curve provides a better fitting between %T and AU [55,60] and showed negative values of %T for AU below 26, indicating that %T was zero; above 400 AU, the %T was 84%, in accordance with others [55,60]. Our data is in accordance with other studies reporting that the levels of DNA breaks and oxidative DNA lesions, measured by the comet assay, are higher in dialysis patients then in controls [77].…”
Section: Dna Damage In Esrd Patientssupporting
confidence: 91%
“…We also found that %T was negatively correlated (Spearman's rank correlation) with CRP (r = −0.368; P = 0.021) and ferritin (r = −0.404; P = 0.011), in ESRD patients; no significant correlations were found between DNA lesions and the rhEPO dose used to treat anemia (r = 0.171; P = 0.306), or the time of HD treatment (r = −0.186; P = 0.256). In a cross-sectional study, the oxidative DNA lesions found in dialysis patients were inversely correlated with the duration of the dialysis sessions [77,78]. We did not find significant differences in DNA damage (comet tail length or tail intensity) for diabetics and nondiabetic ESRD patients, as reported by Ersson et al [77]; however, our findings are in accordance with Mamur et al, reporting no difference in comet tail length or tail intensity between diabetic and non-diabetic ESRD patients on HD [78].…”
Section: Dna Damage In Esrd Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative damage has been attributed to: a) the uremic syndrome itself [14,15], and b) the bio-incompatibility of the haemodialysis membrane [16]. To address this, vitamin E is used for both coating of the haemodialysis membrane [17,18], and as an oral supplementation [19] and has been proven to reduce the recombinant human erythropoietin (rHuEPO) requirement in patients to mitigate anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…We propose GLO1 copy number increase in renal failure is due to dicarbonyl stress and/or hypoxia. Decreased GLO1 copy number in one renal failure patient was likely due to DNA damage induced by uremic toxins [65]. There was no association of increased GLO1 copy number with the common SNP C419A.…”
Section: Discussionmentioning
confidence: 80%